An Empirical Study on How Strategic Plan Interventions Boost Teachers’ Job Satisfaction at Zhanjiang University of Science and Technology in Guangdong Province - Yang, Guochen (Scholar: Human Sciences, 2025)
Purpose: The research explores the impact of school culture, resources, workload, training, and development on teachers’ job satisfaction in private undergraduate universities and identifies significant differences between variables. The key constructs are school culture, resources, workload, training and development, and teachers’ job satisfaction. Research Design, Data, and Methods: The research used the Index of Item-Objective Congruence (IOC) to test validity and Cronbach’s alpha coefficient (n=30) to test reliability. We collected valid questionnaires from 70 teachers at Zhanjiang University of Science and Technology and verified the significant relationship between variables through multiple linear regression (MLR) analysis. Subsequently, 30 teachers were selected to participate in a 24-week strategic plan, and paired sample T-tests were used to analyze the implementation effectiveness of the strategic plan. Result: In the multiple linear regression (MLR) analysis, we found that school culture, resources, workload, training, and development have a significant impact on teachers’ job satisfaction. The paired sample T-test results show significant differences in teachers’ job satisfaction and its influencing variables before and after the implementation of strategic plans. Conclusion: Improving school culture, resources, workload, training, and development can enhance teachers’ job satisfaction. The continuous improvement of job satisfaction among teachers in private undergraduate universities requires collaborative efforts from the government, schools, teachers, and various sectors of society.